The Distinct Role of the Extra-Large G Protein ɑ-Subunit XLɑs - Wang, Yan; Tian, Haoming; Chen, Xiang (Calcified tissue international, 2020)
GNAS is one of the most complex gene loci in the human genome and encodes multiple gene products including Gsα , XLαs , NESP55 , A/B , and AS transcripts. XLαs, the extra-large G protein ɑ-subunit, is paternally expressed. XLɑs and Gsɑ share the common 2–13 exons with different promoters and first exons. Therefore, XLɑs contains most of the functional domains of Gsα including receptor and effector binding sites. In vitro studies suggest a “Gsɑ”-like function of XLɑs regarding the stimulation of cAMP generation in response to receptor activation with different cellular actions. However, it is unclear whether XLαs has an important physiological function in humans. Pseudopseudohypoparathyroidism (PPHP) and progressive osseous heteroplasia (POH) are caused by paternally inherited mutations of GNAS . Maternal uniparental disomy of chromosome 20 [UPD(20)mat] lacks paternal chromosome 20. Therefore, the phenotypes of these diseases may be secondary to the abnormal functions of XLɑs, at least partly. From the phenotypes of human diseases like PPHP, POH, and UPD(20)mat, as well as some animal models with deficient XLɑs functions, it could be seen that XLɑs is involved in the growth and development of the mammalian fetus, plays a different role in glucose, lipid, and energy metabolism when compared with Gsɑ, and could prevent heterotopic ossification in humans and mice. More in vivo and in vitro studies, especially the development of conditional XLɑs knockout mice, are needed to clarify the physiopathologic roles and related signal pathways of XLɑs.